Elevated Rates of Tidal Disruption Events in Active Galactic Nuclei - Karamveer Kaur; Nicholas C. Stone (The Astrophysical Journal)
Advances in time domain astronomy have produced a growing population of flares from galactic nuclei, including both tidal disruption events (TDEs) and flares in active galactic nuclei (AGN). Because TDEs are uncommon and AGN variability is abundant, large-amplitude AGN flares are usually not categorized as TDEs. While TDEs are normally channelled by the collisional process of two-body scatterings over a relaxation timescale, the quadrupole moment of a gas disk alters the stellar orbits, allowing them to collisionlessly approach the central massive black hole (MBH). This leads to an effectively enlarged loss cone, the loss wedge. Earlier studies found a moderate enhancement, up to a factor ~2–3, of TDE rates ${\dot{N}}_{{\rm{2b}}}$ for a static axisymmetric perturbation. Here, we study the loss wedge problem for an evolving AGN disk, which can capture large number of stars into the growing loss wedge over much shorter times. The rates ${\dot{N}}_{{\rm{cl}}}$ of collisionless TDEs produced by these time-evolving disks are much higher than the collisional rates ${\dot{N}}_{{\rm{2b}}}$ in a static loss wedge. We calculate the response of a stellar population to the axisymmetric potential of an adiabatically growing AGN disk and find that the highest rates of collisionless TDEs are achieved for the largest (i) MBH masses M _• and (ii) disk masses M _d . For M _• ~ 10 ^7 M _⊙ and M _d ~ 0.1 M _• , the rate enhancement can be up to a factor ${\dot{N}}_{{\rm{cl}}}/{\dot{N}}_{{\rm{2b}}}\unicode{x0007E}10$ . The orbits of collisionless TDEs sometimes have a preferred orientation in apses, carrying implications for observational signatures of resulting flares.